Rapid Loss of Dissolved CO2 From a Subtropical Steep Headwater Stream - Chan, Chun Ngai; Tsang, Cheuk Lam; Lee, Frederick; Liu, Boyi; Ran, Lishan (Frontiers in Earth Science, 2021)
High-gradient headwater streams are major participants in the carbon (C) cycle because of their capabilities of emitting a significant amount of carbon dioxide (CO2). Notwithstanding, their CO2 emissions have been largely overlooked in previous studies owing to their small water surface area and are sometimes strenuous to be measured because of their narrow channel widths and strong turbulence. This study examined the spatial and seasonal variabilities of CO2 dynamics of a subtropical steep headwater stream fed by groundwater. Our study found that the pH and dissolved oxygen (DO) exhibited a general increasing trend away from the source of the headwater whereas the partial pressure of carbon dioxide (pCO2) showed a downward trend. The stream water pCO2 in the upper reach was found to be higher than the ambient level by 19 – 114 times, with an average drop of > 70% at just 9.2 m from the groundwater source, demonstrating the potentially large emission of CO2 into the atmosphere within this short distance. Additionally, the sampling works conducted further downstream revealed that the CO2 derived from groundwater could almost completely dissipate within approximately half a kilometer downstream of the source. The concentrations of dissolved organic carbon (DOC) and pCO2 were also lower during the period with lower air temperatures in the headwater stream, indicating temperature-dependent metabolism and decomposition of organic matter in soil might modulate the C dynamics in the headwater stream, although the rapid gas exchange along the stream remained the determinative factor. Our findings reassert that headwater streams are an essential source of CO2 and disregarding them from the studies of greenhouse gas emissions of inland waters would underestimate their potency to influence the global C cycle.